Inclusive Storytelling as Destination Communication: Narrative Paradigms and Brand Meaning in Bandung's Urban Walking Tour - Wa Ode Seprina; A. Hasan Al Husain; Supina (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The post-pandemic resurgence of urban walking tours has positioned storytelling as a core form of destination communication, yet the narrative mechanisms through which such tours construct city brand meaning remain theoretically underexplored. This study examines inclusive storytelling practices in Berita Bandung walking tours as a form of destination communication that produces brand meaning for the city. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with guides and participants, participatory observation, and digital document analysis. Two complementary theoretical frameworks were applied: the Narrative Paradigm (Fisher, 1984) to evaluate narrative quality through coherence and fidelity, and Narrative Transportation (Green & Brock, 2000) to explain participants' immersive experience. Findings show that narrative coherence is constructed through research, curation, and route design functioning as a storyline; narrative fidelity is strengthened by human story representation and adaptive dialogue delivery; and narrative transportation emerges as an embodied experience when stories are told at original sites within an egalitarian group dynamic. Together, these mechanisms produce a measurable shift in Bandung's brand meaning, from associations with popular icons toward a layered city that is trusted, felt, and retained. The study argues that inclusive storytelling operates as communicative work that generates brand associations, brand trust, brand attachment, and brand advocacy through repeated micro-experiences in urban space.